CSR performance and CSR in marketing: An analysis with reference to UK retailers and energy providers - Nemeth, Judit Mariann (2008)
The World went through immense changes in the last decade. Globalization, and the appearance of global corporations, was one phenomenon characterizing the era. The growing power and the increasing role in taking on responsibilities originally belonging to governments lead to increased public concerns and scrutiny and that Corporate Social Responsibility (CSR) and sustainability are one of the most fashionable topics today. In line with these trends, we can observe a growth in the communication of companies around CSR, which lead to an increasing interest in the research of this area. Recent research suggests that CSR can be a good tool to enhance firms, legitimacy as well as to develop positive social responsibility image. However on the other hand a growing number of criticisms also seem to appear. Critiques claim that CSR is just a mere PR practice. To bring clarity in this not widely researched area, the dissertation investigates the question, if there is a gap between the CSR performance of the companies and the intensity of their CSR communication targeted at customer or not, by evaluating the CSR performance of eight companies, and contrasting it with the marketing and communication intensity on messages containing CSR claims. In both case a ranking was developed and contrasted. An analysis revealed that the intensity of critique and concern made about the misuses of CSR element in marketing seem to be extreme. Despite the obvious problematic cases the majority of companies communicated in relative balance to its actual CSR performance. Websites were a popular channel to communicate social responsibility credentials in both industries. However, the communication in newspapers was solely a characteristic of companies operating in the gas and electricity industry.